A Multicenter Study of Invasive Fungal Infections in Patients with Childhood-onset Systemic Lupus Erythematosus - Silva, Marco F.; Ferriani, Mariana P.; Terreri, Maria T.; Pereira, Rosa M.; Magalhaes, Claudia S. [UNESP]; Bonfa, Eloisa; Campos, Lucia M.; Okuda, Eunice M.; Appenzeller, Simone; Ferriani, Virginia P.; Barbosa, Cassia M.; Ramos, Valeria C.; et al. (J Rheumatol Publ Co, 2015)
Objective. To study the prevalence, risk factors, and mortality of invasive fungal infections (IFI) in patients with childhood-onset systemic lupus erythematosus (cSLE). Methods. A retrospective multicenter cohort study was performed in 852 patients with cSLE from 10 pediatric rheumatology services. An investigator meeting was held and all participants received database training. IFI were diagnosed according to the European Organization for Research and Treatment of Cancer/Invasive Fungal Infections Cooperative Group and the National Institute of Allergy and Infectious Diseases Mycoses Study Group Consensus Group criteria (proven, probable, and possible). Also evaluated were demographic, clinical, and laboratory data, and disease activity [SLE Disease Activity Index 2000 (SLEDAI-2K)], cumulative damage (Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index), treatment, and outcomes. Results. IFI were observed in 33/852 patients (3.9%) with cSLE. Proven IFI was diagnosed in 22 patients with cSLE, probable IFI in 5, and possible IFI in 6. Types of IFI were candidiasis (20), aspergillosis (9), cryptococcosis (2), and 1 each disseminated histoplasmosis and paracoccidioidomycosis. The median of disease duration was lower (1.0 vs 4.7 yrs, p < 0.0001) with a higher current SLEDAI-2K [19.5 (0-44) vs 2 (0-45), p < 0.0001] and current prednisone (PRED) dose [50 (10-60) vs 10 (2-90) mg/day, p < 0.0001] in patients with IFI compared with those without IFI. The frequency of death was higher in the former group (51% vs 6%, p < 0.0001). Logistic regression analysis revealed that SLEDAI-2K (OR 1.108, 95% CI 1.057-1.163, p < 0.0001), current PRED dose (OR 1.046, 95% CI 1.021-1.071, p < 0.0001), and disease duration (OR 0.984, 95% CI 0.969-0.998, p = 0.030) were independent risk factors for IFI (R-2 Nagelkerke 0.425). Conclusion. To our knowledge, this is the first study to characterize IFI in patients with cSLE. We identified that disease activity and current glucocorticoid use were the main risk factors for these life-threatening infections, mainly in the first years of disease course, with a high rate of fatal outcome.
Keywords: INFECTION; INVASIVE FUNGAL INFECTION; INVASIVE FUNGAL DISEASE; CHILDHOOD-ONSET SYSTEMIC LUPUS ERYTHEMATOSUS; MULTICENTER COHORT